DINAMIKA ZAKAT DALAM TINJAUAN SEJARAH KEINDONESIAAN: KAJIAN POSITIFIKASI DAN IMPLIKASINYA BAGI EKONOMI UMAT - Fikriawan, Suad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2019)
This study aims to outline how it should go back to the era when the charity in terms of its historical context by tracing regulations since the pre-colonial, Kolonia, the old order, a new order and until the era of reform. This study suggests that the zakat law positifikasi believed by many good scholars, Muslim scholars, and charity watchdog, as the best solution for the realization of the optimization of the collection and management of zaka, as one obligation for Muslims. Then the Law no. 38 of 1999 on Zakah Management is aimed at optimizing the distribution of zakat economic equality and development, but it needs to be supported by a business entity Zakah is a modern and professional. Zakah funds should be directed to small businesses run by the majority of the ummah, in this case agriculture, and the livelihoods of the majority of Muslims and people of Indonesia. Thus the charity will be able to influence the economic development of society.